Targeting programmed cell death with natural products: a potential therapeutic strategy for diminished ovarian reserve and fertility preservation - Ju, Wenhan; Zhao, Shuai; Li, Danping; Zhang, Jinfu; Xiang, Shan; Lian, Fang (Frontiers in Pharmacology, 2025)
The depletion of ovarian reserve is a major factor contributing to the decline in female fertility. It is characterized by a simultaneous reduction in the quantity and quality of oocytes and the follicular pools. The cyclic recruitment of primordial follicles and the preservation of oocyte quality involve complex and tightly regulated biological processes. Granulosa cells, which surround the oocytes, play a pivotal role in follicular development and the determination of follicular fate. Programmed cell death (PCD), a genetically regulated process of cell elimination, is a key factor in the regulation of ovarian reserve dynamics. Emerging evidence suggests that natural products derived from medicinal plants, dietary components, animals, and microorganisms may modulate PCD in granulosa cells through various molecular mechanisms and signaling pathways. These natural products have demonstrated preliminary effects in delaying ovarian aging and preserving ovarian reserve in preclinical models. This review discusses the roles and underlying mechanisms of various forms of PCD in diminished ovarian reserve, while summarizing the current findings on natural products that influence granulosa cells PCD to protect ovarian function. These insights may contribute to the future development of novel, targeted strategies aimed at preserving female reproductive potential.